2016
DOI: 10.18632/oncotarget.10767
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics in myeloid derived suppressor cells: a sheathed sword towards cancer

Abstract: Myeloid-derived suppressor cells (MDSCs), a heterogeneous population of cells composed of progenitors and precursors to myeloid cells, are deemed to participate in the development of tumor-favoring immunosuppressive microenvironment. Thus, the regulatory strategies targeting MDSCs' expansion, differentiation, accumulation and function could possibly be effective “weapons” in anti-tumor immunotherapies. Epigenetic mechanisms, which involve DNA modification, covalent histone modification and RNA interference, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 97 publications
0
39
1
Order By: Relevance
“…Major evidence, albeit primarily in murine models, indicates a central role of miR-mediated posttranscriptional regulation in MDSC differentiation and function (40,51). Via in vitro studies on monocyte conditioning, we found that hallmarks of human MDSCs, i.e., downregulation of HLA-DR, secretion of IL-6, TGF-β, and CCL2, and inhibition of T cell proliferation and function (9, 10), can be reconstituted by in vitro cotransfection of the 8 MDSC-miRs; this finding held true even when the requirement was decreased to 4 miRs (miR-146a, miR-100, miR-125b, and miR-155) in some donors (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Major evidence, albeit primarily in murine models, indicates a central role of miR-mediated posttranscriptional regulation in MDSC differentiation and function (40,51). Via in vitro studies on monocyte conditioning, we found that hallmarks of human MDSCs, i.e., downregulation of HLA-DR, secretion of IL-6, TGF-β, and CCL2, and inhibition of T cell proliferation and function (9, 10), can be reconstituted by in vitro cotransfection of the 8 MDSC-miRs; this finding held true even when the requirement was decreased to 4 miRs (miR-146a, miR-100, miR-125b, and miR-155) in some donors (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…MDSCs are a heterogeneous population of cells composed of progenitors and precursors to myeloid cells that exert immunosuppressive effects, subsequently favoring tumor development [14]. The epigenetic programs of MDSCs determine their function, which include DNA and histone modifications as well as modulatory noncoding RNAs [76]. A similar pattern is present when monocytes infiltrate tumors and differentiate into TAMs which promote tumor growth, progression, invasion, and angiogenesis and suppress the antitumoral immune responses [1].…”
Section: Training the Innate Immunity For Adjuvant Cancer Therapymentioning
confidence: 99%
“…Because epigenetic modifications are reversible and susceptible to environmental factors, they may be a promising direction for clinical medicine [ 69 ]. These epigenetic modifications play an important role in the regulation of cancer cells [ 70 ], immunosuppressive cells [ 71 ], and tumor-associated fibroblasts [ 72 ] in the TME. These cells continuously update and reshape through epigenetic modification in response to a series of signals sent by cancer cells, thereby jointly promoting the occurrence, development, and metastasis of tumors.…”
Section: Epigenetic Modification Of Mdscsmentioning
confidence: 99%
“…[ 73 ]. In addition to common DNA methylation and histone modification, Non-Coding RNAs also play an important role in epigenetic modification, especially miRNA and siRNA [ 71 ], and emerging studies have recently identified the role of miRNAs in MDSCs amplification, development, migration, and function [ 70 ]. MDSC-related microRNAs (miR-146a, miR-155, miR-125b, miR-100, let-7e, miR-125A, miR-146b, miR-99b) are associated with the resistance of melanoma patients to immunocheckpoint inhibitor therapy.…”
Section: Epigenetic Modification Of Mdscsmentioning
confidence: 99%
See 1 more Smart Citation